Use of humour as a method of therapeutic intervention with children affected by oncological processes - María FERNÁNDEZ HAWRYLAK; Davinia HERAS SEVILLA; Julia BASTIDA SUSINOS (Ediciones Universidad de Salamanca, 2018)
Clowns in hospitals begin to be common, in particular in the paediatric sphere, becoming a recurring action. Although there are many countries in the world where children receive the performance of clowns during their hospital stay, yet few studies have been devoted to make a deep analysis of the effectiveness of hospital clowns interventions in the adaptation to hospitalization and in the acceptance of the disease. This research aims to check if the use of humour as an active disease coping strategy is effective in children with cancer and their families. Case study was used as research method. The sample consisted of four children affected with oncological diseases, aged between 5 and 8, hospitalized in the paediatric ward of the University Hospital of Burgos and attending the Hospital School, and their families. The instruments used were semi-structured interviews with the families, and an ad hoc designed Likert questionnaire for the children. Data from questionnaires were coded and analysed. The information from the interviews was coded and categorized according to thematic and grammatical criteria. The outcomes show that humour improves the hospital stay of the children and their relatives, gets them distracted and makes them forget their disease for a while. It would be highlighted, in conclusion, that the use of humour does not solve any problem itself, but could change the way of addressing the disease, therefore it is an active form of coping.